P197 Physical Inactivity in Sarcoidosis. (14th November 2013) - Vasudevan, S; Maddocks, M; Chamberlain, S; Spinou, A; Wood, C; Jolley, C; Birring, SS
Abstract : Introduction: Sarcoidosis is associated with dyspnoea, arthralgia, fatigue and poor health status. Little is known about physical activity in sarcoidosis. This study aimed to: 1) objectively measure physical activity in patients with pulmonary sarcoidosis; 2) investigate the relationship between physical activity and fatigue, exercise capacity, health status and lung function. Methods: 15 pulmonary sarcoidosis patients (mean age: 52.7 years; 4 males) and 14 healthy controls (mean age: 46.5 years; 4 males) were recruited. Physical activity was assessed objectively over one week, using a validated tri-axial accelerometer- ActivPal TM, and subjectively with the International Physical Activity Questionnaire (IPAQ). All participants also underwent pulmonary function tests, 6MWT and completed the Fatigue Assessment Scale (FAS), MRC Dyspnoea Scale and the King's Sarcoidosis QOL Questionnaire (KSQ). Results: Compared to controls, patients had lower mean ± SD daily step count (5624 ± 1875 steps vs. 10429 ± 2942 steps, p < 0.01, figure 1 ) and time spent stepping (1.18 ± 0.35 hr.day -1 vs. 1.97 ± 0.46 hr.day -1 ; p < 0.01). There was also a trend to reduced bouts of activity in sarcoidosis patients compared with controls, (sit-stand transitions: 49 ± 15 vs. 61 ± 20; p = 0.08). Exercise capacity was significantly reduced in patients compared to controls (6MWT distance: 375 ± 59 m vs. 487 ± 92 m; p < 0.01). There was a significant association between daily step counts, and 6MWT distance, of patients (r = 0.63, p = 0.01). Physical activity (overall) reported subjectively was not significantly different between groups (Overall IPAQ median score: 2153 vs. 3230 MET.min.week-1; p = 0.32). However, 87% of patients reported doing no vigorous physical activity compared to 50% in controls (vigorous activity IPAQ; p < 0.01). There were no significant correlations between daily step count and fatigue, dyspnoea, health status, lung function and self reported physical activity (IPAQ). Conclusion: Physical activity is significantly reduced in sarcoidosis compared to healthy subjects. Objective measures of physical activity assess a unique dimension of health in the patient's own environment that is not captured by existing clinical tools and should be further investigated.